Communities of play : emergent cultures in multiplayer games and virtual worlds - Pearce, Celia (Cambridge, Mass. : MIT Press, 2009)
- Methods of culture / Tom Boellstorff ##- Play, community, and history / Bonnie A. Nardi ##- Play, community, and emergent cultures ##- Communities of play and the global playground ##- Virtual worlds, play ecosystems, and the ludisphere ##- Emergence in cultures, games, and virtual worlds ##- Reading, writing, and playing cultures ##- An imaginary homeland ##- Identity as place ##- The inner lives of avatars ##- Communities and cultures of play ##- Patterns of emergence ##- Productive play : cultural production, meaning-making, and agency ##- Porous magic circles and the ludisphere ##- Emergence as design material ##- Methodology : playing ethnography ##- Being Artemesia : my life as an avatar ##- Coda: Uru resurrection : applied cyberethnography as action research ##- Crafting cultures : emergence as design material ##- Global playgrounds and the "play turn" in culture.
Includes bibliographical references and index.
boek